Evaluation of Training Effectiveness of Kirkpatrick Model on Blended Learning and Classical Training in Sarolangun District Government - Sulistiyono, Arif; Ginting, Ginta; Khalid, Idham (Golden Ratio of Human Resource Management, 2025)
This research aims to evaluate the effectiveness of the Kirkpatrick training model in leadership training for supervisors in the Sarolangun Regency Government. The study compares the effectiveness of supervisor leadership training conducted using classical methods and blended learning methods. A quantitative comparative research method is employed. The study's population comprises 80 individuals for training evaluation at levels 1 and 2, and 160 individuals for training evaluation at levels 3 and 4. Primary and secondary data sources are utilized. Data collection techniques include interviews, questionnaires, and documentation. The Likert scale measurement is conducted using Microsoft Excel, and hypothesis testing is performed using SPSS 26.0 software. The results indicate that the evaluation using the Kirkpatrick model between blended learning and classical methods obtained a P value (0.523 > 0.05), indicating that Ho is accepted and Ha is rejected. This means there is no significant difference in the Kirkpatrick model evaluation results between training using blended learning methods and classical methods.